His right hand - Harrison, Mette Ivie, 1970- (Harrison, Mette Ivie, 1970- Linda Wallheim mystery, 2015)
The tight-knit Mormon community in Draper, Utah is thrown into upheaval when their ward's second counselor-- one of the bishop's right-hand men-- is found dead in an elaborately staged murder on church property. Linda Wallheim, the wife of the ward's bishop, is worried about Carl's grieving family. When the autopsy report reveals Carl Ashby was a biological female, Church officials are more concerned with hushing up the story than solving the crime. What else was he hiding-- and can Linda ferret out the key to his death before the rumors tear her community apart?